2010
DOI: 10.1063/1.3354112
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transitions in a three dimensional associating lattice gas model

Abstract: Two interacting particles in a spherical pore J. Chem. Phys. 134, 064508 (2011) Thermodynamical approach to sympathetic cooling of neutral particles J. Chem. Phys. 134, 044109 (2011) We investigate the thermodynamic and dynamic properties of a three dimensional associating lattice gas ͑ALG͒ model through Monte Carlo simulations. The ALG model combines a soft core potential and orientational degrees of freedom. The competition of directional attractive forces and the soft core potential results in two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 25 publications
(36 reference statements)
1
37
0
Order By: Relevance
“…This is different from the behavior presented by liquid water, but is common to other lattice models. 15,16,27 A possible reason for this discrepancy is the fact that bonding is more rigid in the lattice model, thus reducing the mobility of particles as compared to continuous models, in which rotations allow for slightly distorted bonds.…”
Section: A Diffusion Anomalymentioning
confidence: 99%
See 1 more Smart Citation
“…This is different from the behavior presented by liquid water, but is common to other lattice models. 15,16,27 A possible reason for this discrepancy is the fact that bonding is more rigid in the lattice model, thus reducing the mobility of particles as compared to continuous models, in which rotations allow for slightly distorted bonds.…”
Section: A Diffusion Anomalymentioning
confidence: 99%
“…In order to address this question, a number of models which display criticality were investigated as to the presence of fragile-to-strong transitions. [14][15][16] These studies have shown that on crossing the critical line, fragile-to-strong, strong-to-strong, or even fragile-to-fragile transitions could be observed, depending on the specific structure of the phases separated by the critical line. In the particular case of the associated lattice gas model ͑ALG͒, which presents two critical lines, two kinds of dynamic transitions are also present.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Even though there are a number of two and three dimensional lattice models that would in principle exhibit the anomalies present in water, 6,16,[19][20][21] here water is represented by the associating lattice gas (ALG) (Refs. [22][23][24][25][26][27][28]) that has already shown the density and diffusion anomalies described above. The ALG does not have the full complexity of the molecular liquid, however it leads to a network-forming fluid in which directionality plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…26 Dynamic and thermodynamic properties of the system were previously obtained by Monte Carlo simulations 26,28,29 and analytical methods. 30 The model consists of a body centered cubic lattice where sites can be either occupied (σ i = 1) by a water molecule or empty (σ i = 0).…”
Section: The Pure Water Model: Algmentioning
confidence: 99%
“…Both models present several of the anomalous features of water [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, the second kind of model does not involve specific orientation of low-energy pairs of particles: pair energy is controlled by distance, not by orientation.…”
Section: Introductionmentioning
confidence: 99%